Trinidad Beauty, Trinidad, W.I. - Norton, Noel (T. Geddes Grant (Trinidad) LTD., Trinidad, Printed by Syncreators Ltd., 2008)
Photo of an Creole Woman with head wrap and cultural earrings. Includes a 15 cent Trinidad and Tobago postage dated 14th November. Addressed to the Cromwell Family in the U.S.A
Colour:Various colours ; Style:Portrait ; Other:Unbordered, Undivided
Addressed to Cornwell Family, 40 Cummings Ave., Wollaston, Massachusetts, USA.
Keywords: Postcards; Creole--Woman; Headgear--Africa; Ethnic costume--Africa